1953
DOI: 10.1021/ja01113a043
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Chichibabin Reactions. The Condensation of Phenylacetaldehyde and Homoveratric Aldehyde with Ammonia1

Abstract: filtering and adding petroleum ether. The recrystallized material exhibited dimorphism, melting at 178.3°, resolidifying and melting again at 191°.14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1960
1960
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…A plausible mechanism is proposed in Scheme 2 that is based on previous reports 19,20 combined with our experiments results. Initially, the condensation of the acetophenone with itself gives A, which then undergoes a Michael Addition with another molecule of acetophenone leading to 1,5-dicarbonyl compound B. Condensation reaction of B in the presence of ammonium acetate affords dihydropyridine intermediates C and D. Oxidative aromatization with removal of methane from C would yield 2,4,6-triarylpyridine G, and D forms another two dihydropyridine intermediates E and F by removal of the methyl group.…”
Section: Scheme 1 Simple Selective Synthesis Of 24-and 26-diarylpyrsupporting
confidence: 63%
See 1 more Smart Citation
“…A plausible mechanism is proposed in Scheme 2 that is based on previous reports 19,20 combined with our experiments results. Initially, the condensation of the acetophenone with itself gives A, which then undergoes a Michael Addition with another molecule of acetophenone leading to 1,5-dicarbonyl compound B. Condensation reaction of B in the presence of ammonium acetate affords dihydropyridine intermediates C and D. Oxidative aromatization with removal of methane from C would yield 2,4,6-triarylpyridine G, and D forms another two dihydropyridine intermediates E and F by removal of the methyl group.…”
Section: Scheme 1 Simple Selective Synthesis Of 24-and 26-diarylpyrsupporting
confidence: 63%
“…In 1953, Ernest L. Eliel et al reported a condensation reaction of phenylacetaldehyde with ammonia, 19 which was considered to be an abnormal Chichibabin reaction because of its unexpected 3,5-diphenylpyridine product. Perhaps because of its inefficiency, to the best of our knowledge, there have been few investigations on the utility of this reaction for the synthesis of diarylpyridines.…”
mentioning
confidence: 99%
“…The products of this reaction correspond to those of the "abnormal" Chichibabin pyridine synthesis-a variant that, until now, was not synthetically useful. [7] This approach represents the first mild one-pot route to such 3,5-diarylpyridine systems (known bioactive agents [8] ) that does not require prefunctionalized heterocycles.…”
mentioning
confidence: 99%
“…The reaction involves the condensation of aldehydes with an amine to yield pyridiniums in a single synthetic step. Initially, the reaction required elevated temperatures and pressure, or acid catalysis [ 12 , 13 , 14 , 15 , 16 , 17 ], but the intrinsic instability of aldehydes under these forcing conditions often resulted in product yields that were at best mediocre.…”
Section: Introductionmentioning
confidence: 99%